The morphological and mineralogical characteristics and thermal conductivity of ash deposits in a 220 MW CFBB firing Zhundong lignite. (15th January 2023) - Long, Xiaofei; Li, Jianbo; Wang, Hongjian; Liang, Yintang; Lu, Xiaofeng; Zhang, Dongke
Abstract: Formation of ash deposit on heat transfer surfaces during Zhundong lignite (ZD) combustion in circulating fluidized bed (CFB) boiler has affected boiler operation and its thermal efficiency. This work therefore characterised the morphology, mineralogy and thermal conductivity of the ash deposits in a 220 MW CFB boiler firing ZD for an improved understanding of deposit characteristics. By using XRF, SEM-EDS, XRD, and laser conductometer, results revealed that deposits on superheaters and reheaters were as thick as 3.0–4.5 cm. Moreover, the inner layer of the deposits consisted of fine ash particles enriching in Na, Ca and S in the forms of Na2 SO4, CaSO4, and Na2 Ca(SO4 )2, whereas the outer layer comprising CaSO4, Na6 Ca2 Al6 Si6 O24 (SO4 )2, Fe2 O3, SiO2 and Mg2 SiO4 with more SiO2 and Al2 O3 presented. Besides, thermal conductivity of the inner layer was ca. 1.83 W/(m · K), and that of the middle layer with an increased pore size was ca. 1.50 W/(m · K), both of them were independent of temperature at 550–900 °C and overweighed the out layer being 0.65–0.82 W/(m · K). This would lead to an increase in coal consumption of ca. 12.9%, highlighting the severity of deposit build-up in adversely impacting the heat transfers and deteriorating the fuel economics during ZD CFB combustion. Highlights: Morphology, mineralogy and thermal conductivity of deposits in a CFB characterised. Deposit at the inner layer enriching in Na2 SO4, CaSO4 and Na2 Ca(SO4 )2 was sintered. Deposits at the outer layer had more SiO2 and Al2 O3 and an increased pore volume. Thermal conductivity of sintered inner layer was the highest regardless temperature. An extra amount of coal up to 12.9% has to be burnt as a result of deposit build up.